Türk Diasporası Kavramına Eleştirel Bir Bakış: Türk Diasporası Var mı? - Yaldiz, Fırat (Bilig, Journal of Social Sciences of Turkish World, 2019)
In this article, the content of the term of Turkish Diaspora which is frequently being used in political, bureaucratical and academic life is being discussed. Particularly, usage of the term Turkish in between citizenship and kinship meanings, and out of the scope of the constitutional and legal definition makes the term Turkish Diaspora more problematic. It is unclear what is meant by the term Turkish diaspora that is being broadly and indefinitely used, and who are the subjects of Turkish diaspora. Moreover, Turkey’s expectations and implications in her foreign policy regarding the societies which she defines them as diaspora is getting more problematic and important day by day. Despite the enormous scope of the problem, relatively little academic research has been conducted on this subject. This article, with the social constructionist perspective will discuss the phenomenon of Turkish Diaspora.

Bu makalede, Türkiye’nin siyasi, bürokratik ve akademik hayatında sıklıkla kullanılan Türk Diasporası kavramının içeriği tartışılmaktadır. Özellikle Türk kavramının, vatandaşlık ve soydaşlık arasında, anayasal düzenlemelerin de ötesine geçerek kullanılması, “Türk Diasporası” kavramını sorunlu hale getirmektedir. Çok geniş ve belirsiz bir içerikle kullanılmakta olan bu kavram ile ne ifade edildiği ve kimlerin Türk diasporasının öznesi olduğu belli değildir. Üstelik Türkiye’nin diaspora olarak adlandırdığı toplumlara ilişkin dış politik beklenti ve uygulamaları her geçen gün daha sorunlu ve önemli bir hale gelmekte; ancak bu konuya ilişkin yeterli seviyede akademik araştırma bulunmamaktadır.
Keywords: Migration; diaspora; Türk; Türk diasporası; soydaş; vatandaş; Migration; diaspora; Turkish; Turkish diaspora; fellow descendants; citizen